ANSWER
![\frac{3}{4} z + 6 = \frac{3}{4} (z + 8 )](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20z%20%2B%206%20%3D%20%20%5Cfrac%7B3%7D%7B4%7D%20%28z%20%2B%20%208%20%20%29)
EXPLANATION
We want to factor
![\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20)
out of
![\frac{3}{4} z + 6](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20z%20%2B%206)
The first term is already having a factor of
![\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20)
The constant term which is the second term is not having a factor of
![\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20)
so we need to use a trick of multiplying and dividing by the same factor to obtain,
![\frac{3}{4} z + 6 = \frac{3}{4} z + \frac{3}{4} \times \frac{6}{ \frac{3}{4} }](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20z%20%2B%206%20%3D%20%20%5Cfrac%7B3%7D%7B4%7D%20z%20%2B%20%20%5Cfrac%7B3%7D%7B4%7D%20%20%5Ctimes%20%20%5Cfrac%7B6%7D%7B%20%5Cfrac%7B3%7D%7B4%7D%20%7D%20)
We can now factor
![\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20)
out of the right hand side to obtain,
![\frac{3}{4} z + 6 = \frac{3}{4} (z + \frac{6}{ \frac{3}{4} } )](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20z%20%2B%206%20%3D%20%20%5Cfrac%7B3%7D%7B4%7D%20%28z%20%2B%20%20%5Cfrac%7B6%7D%7B%20%5Cfrac%7B3%7D%7B4%7D%20%7D%20%29)
Let us rewrite the right most fraction using the normal division symbol.
![\frac{3}{4} z + 6 = \frac{3}{4} (z + 6 \div \frac{3}{4} )](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20z%20%2B%206%20%3D%20%20%5Cfrac%7B3%7D%7B4%7D%20%28z%20%2B%20%206%20%5Cdiv%20%20%5Cfrac%7B3%7D%7B4%7D%20%20%29)
We simplify to obtain,
![\frac{3}{4} z + 6 = \frac{3}{4} (z + 6 \times \frac{4}{3} )](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20z%20%2B%206%20%3D%20%20%5Cfrac%7B3%7D%7B4%7D%20%28z%20%2B%20%206%20%20%5Ctimes%20%20%5Cfrac%7B4%7D%7B3%7D%20%20%29)
This further gives us,
![\frac{3}{4} z + 6 = \frac{3}{4} (z + 2 \times 4 )](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20z%20%2B%206%20%3D%20%20%5Cfrac%7B3%7D%7B4%7D%20%28z%20%2B%20%202%20%5Ctimes%20%204%20%20%29)
Answer:
18.9
Step-by-step explanation:
21+(-3)-(-0.9) = 21-3+0.9 = 18+0.9 = 18.9
Answer:
Step-by-step explanation:
Your cousin wants to buy a coat and can spend at most $95. This means that the total amount of money that he can spend in buying the coat would be lesser than or equal to $95.
He has a coupon for $20 off any coat. Let x represent the cost of the coat. The amount that he can pay for the coat will be x - 20.
The inequality to find the original prices of coats he can afford would be
x - 20 lesser than or equal to 95
X^2-X-6=(X-3)(X+2)
(X+2)/(x+2)=1
Which just leaves (x-3)
X=3
540 is the answer because the doubled the first number to get the second number and multiplyed that by 3 to get the third number